1989
DOI: 10.1182/blood.v74.1.115.115
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of tumor-induced neutrophilia: constitutive production of colony-stimulating factors and their synergistic actions

Abstract: Transplantation of a murine mammary carcinoma (CE maca) into mice induces marked granulocytosis and hypercalcemia secondary to excessive bone resorption. Such responses are not induced by another murine mammary carcinoma Bc66. In order to understand the mechanisms of these unique phenomena, we analyzed mRNA of tumor cells for expression of murine granulopoietic growth factors and studied interactions of tumor- derived factors using antiserum to a growth factor in vitro and in vivo. The Northern blot analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…9,10 These cytokines tend to promote tumor growth in a paracrine manner. 8,11 Neutrophilia driven by leukogenic cytokines produced by tumor cells was also observed in nude mice upon tumor cells transplantation. 12,13 Eosinophilia can be a manifestation of a myriad of causes such as infections, drug reactions allergic, and autoimmune processes.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 These cytokines tend to promote tumor growth in a paracrine manner. 8,11 Neutrophilia driven by leukogenic cytokines produced by tumor cells was also observed in nude mice upon tumor cells transplantation. 12,13 Eosinophilia can be a manifestation of a myriad of causes such as infections, drug reactions allergic, and autoimmune processes.…”
Section: Discussionmentioning
confidence: 99%
“…Marrow granulocytic hyperplasia is associated with an increase in the number of osteoclasts lining endosteal surfaces and increased bone resorption [ 151 , 152 ]. Granulocyte colony stimulating factor (G-CSF) and macrophage colony stimulating factor (M-CSF) were detected by Northern blot analysis in CE maca tumors and treatment with anti-M-CSF reduced the neutrophilia, but did not affect the hypercalcemia [ 153 ]. Granulocytic hyperplasia has been associated with increased osteoclasts and osteoclast activity [ 154 ].…”
Section: Mouse Models Of Cahmentioning
confidence: 99%
“…One possible mechanism is the production of soluble factors such as granulocyte and macrophage colony stimulating factor (GM-CSF) by tumor cells, capable of mobilizing precursors in the bone marrow; or vascular endothelial growth factor (VEGF) and interleukin-6, both of which alter cell differentiation [30]. It was demonstrated that G-CSF and M-CSF are produced constitutively in murine mammary carcinoma cells, and that these factors act synergistically to stimulate granulocytes in vitro; this synergism may play a role in the marked granulocytosis observed in tumor-bearing animals [41].…”
Section: Mechanisms Involved In Leukocyte Alterations In Cancer Patientsmentioning
confidence: 99%